Hallazgos hematológicos y detección de anticuerpos contra Anaplasma spp en perros con antecedentes de garrapatas en el distrito de Chiclayo (Lambayeque, Perú) - Alvarez M., Grecia (2020)
The aim of this study was to determine the presence of canine anaplasmosis by haematological findings (evidence of inclusion bodies or morulae in blood smear plus thrombocytopenia) and the presence of antibodies against Anaplasma spp in dogs with a history of ticks from the Chiclayo district (Lambayeque, Peru). Blood samples (n=88) were collected from apparently healthy dogs with a history of ticks. The haematological findings showed that 2.3% (2/88) of dogs were positive (with inclusion bodies or morulae plus thrombocytopenia) being compatible with A. platys. In addition, 22.7% (20/88) seropositivity against Anaplasma spp and a multiple seropositivity of 21.6% (19/88) with Ehrlichia spp were detected by the SNAP 4Dx Plus Test. Positive and seropositive dogs showed thrombocytopenia and, to a lesser extent, anaemia, leucocytosis and leukopenia. The results showed presence of subclinical canine anaplasmosis in dogs with a history of ticks in the Chiclayo district.